2013
DOI: 10.1155/2013/140210
|View full text |Cite
|
Sign up to set email alerts
|

The Gilles De La Tourette Syndrome-Quality of Life Scale for Children and Adolescents (C&A-GTS-QOL): Development and Validation of the Italian Version

Abstract: Background: Gilles de la Tourette syndrome (GTS) is a chronic childhood-onset neuropsychiatric disorder with a significant impact on patients’ health-related quality of life (HR-QOL). Cavanna et al. (Neurology 2008; 71: 1410–1416) developed and validated the first disease-specific HR-QOL assessment tool for adults with GTS (Gilles de la Tourette Syndrome-Quality of Life Scale, GTS-QOL). This paper presents the translation, adaptation and validation of the GTS-QOL for young Italian patients with GTS. Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 16 publications
2
52
0
Order By: Relevance
“…As part of this assessment, youth's quality of life should be evaluated using either general quality of life measures that have demonstrated adequate psychometric properties in youth with CTD (Storch et al, 2007b), or more CTD specific quality of life measures (Cavanna et al, 2008). While CTD specific quality of life measures have demonstrated adequate psychometric properties in Italian youth with CTD (Cavanna et al, 2013a; Cavanna et al, 2013b), such measures still require further psychometric validation in English-speaking youth with CTD prior to their widespread use. After a thorough evaluation and clarification of treatment goals, clinical guidelines should be followed for youth and families seeking reductions in tic symptom severity (Murphy et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As part of this assessment, youth's quality of life should be evaluated using either general quality of life measures that have demonstrated adequate psychometric properties in youth with CTD (Storch et al, 2007b), or more CTD specific quality of life measures (Cavanna et al, 2008). While CTD specific quality of life measures have demonstrated adequate psychometric properties in Italian youth with CTD (Cavanna et al, 2013a; Cavanna et al, 2013b), such measures still require further psychometric validation in English-speaking youth with CTD prior to their widespread use. After a thorough evaluation and clarification of treatment goals, clinical guidelines should be followed for youth and families seeking reductions in tic symptom severity (Murphy et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The current findings support the importance of assessing the impact of both tics and co-morbidities on well-being, and using this information to guide interventions. A disease-specific health-related quality-of-life measure for young people with Tourette syndrome has recently been developed and validated for this purpose (Cavanna et al 2013b), and has demonstrated sensitivity to the differential impact of some co-morbidities (Cavanna et al 2013c).…”
Section: Discussionmentioning
confidence: 99%
“…As a subjective marker of well-being, QoL has emerged during the past 15 years as an important component in understanding the experience of patients with GTS, and as a key assessment and treatment target in its own right. Several GTS-specific tools have been developed that will facilitate the incorporation of QoL into research studies and clinical practice 184,185 . The field of GTS genetics is poised for an upsurge in discovery of definitive GTS susceptibility genes in the next five years.…”
Section: Thoughts For Dougmentioning
confidence: 99%